Mental Motivation and Its Relationship with Mind Habits for A Sample of Secondary School Students in Jeddah - Alshehri, Fatimah Abdullah; Abaalkhail, Amnah Abdulaziz (Journal of Educational and Psychological Sciences, 2021)
The study aimed to detect the level of mental motivation and habits of mind; to examine the relation between mental motivation, its dimensions and between habits of mind and also aimed to identify the differences between the average degrees of students in mental motivation and habits of mind according to the academic specialization (Science - Literature). The study sample consisted of (379) second and third grade female students in the secondary stage in Jeddah who were selected by random stratified method. To achieve the study objectives, the researcher used the descriptive comparative correlational approach; two tools were used: The California measure of mental motivation (CM3ll) for the secondary stage, Shuihi translation (2016) and habits of mind measure according to Costa & Kallick model of Carl Rodgers, Novell translation (2008). The results of the study found that secondary school female students have a high level of mental motivation, a very high level of habits of mind. In addition, there is a statistically significant correlation between motivation, its dimensions and habits of mind. The dimensions of mental motivation contributed to the interpretation of the variation of the habits of the mind by (57%) which was respectively arranged as follows: problem-solving creatively by habits of mind, the factor of mental focus and then the factor of orientation towards learning; while the cognitive integration factor did not show significance to the prediction of habits of mind. The results also revealed that there were statistically significant differences among secondary school female students in mental motivation attributed to specialization in favor of students of science section; while there are no statistically significant differences in the habits of mind between female students of Science and Literature sections. The study recommended the need of taking care of providing students with cognitive and supra-cognitive thinking skills by educational institutions also, creating the appropriate educational environment for practicing them to prepare an effective and efficient citizen who can face the problems and requirements of different aspects of life.
Keywords: Mental Motivation; Habits of Mind; High School students